Morphological and mechanical properties of rubber-toughened polyamide 6/ polypropylene nanocomposites prepared by different methods of compounding - Wahit, Mat Uzir (Sage Publication, 2006)
The nanocomposites based on polyamide 6/polypropylene blends (PA6/PP), polypropylene grafted with maleic anhydride (PPgMAH), ethylene octene copolymer (POE), and organically modified montmorillonite (organoclay) are prepared through different mixing sequences of melt intercalation technique. The processes used are: (1) direct melt intercalation single extrusion process (SD), (2) two times direct melt intercalation (S2x), (3) two steps melt intercalation i.e., mixing of preblend PA6/organoclay with preblend PP/PPgMAH/POE (S2sa), and (4) two steps melt intercalation i.e., mixing of preblend PA6/PP/PPgMAH/organoclay with POE (S2sb). The effect of various processing techniques on the structural, morphological, and mechanical properties of nanocomposites is characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), tensile, flexural, and Izod impact testing. The results show that all the methods give generally exfoliated structures based on XRD. It is also found that the melt intercalation technique significantly influences the dispersion behavior of POE in the PA6/PP matrix and thus the impact properties. However, no significant blending sequence effect is found for tensile and flexural properties of nanocomposites. Overall, the method S2sa gives the best mechanical properties due to its good dispersion of organoclays and elastomer in the continuous PA6/PP matrix.